Sodium trithiocarbonate cathode for high-performance sodium–sulfur batteries. Issue 1 (8th December 2022) - Sul, Hyunki; Bhargav, Amruth; Manthiram, Arumugam
Abstract : A sodium trithiocarbonate cathode enables the formation of a protective layer in situ on both the cathode and anode, which greatly enhances the cell rate performance and cycle life of Na–S batteries. Abstract : The high abundance and low cost of sodium and sulfur make room-temperature sodium–sulfur (RT Na–S) batteries an attractive technology compared to the current lithium-ion batteries for large-scale grid-storage applications. However, the commercialization of RT Na–S batteries is impeded by the slow kinetics of Na–S chemistry, severe sodium polysulfide shuttling, and uncontrollable growth of dendritic Na. Herein, sodium trithiocarbonate (Na2 CS3 ) is applied as a cathode material to facilitate concurrent improvement in both electrodes, leading to a high-rate performance with an extended cycle life. The conductive characteristic of the carbon–sulfur resonance bond enables fast ion and electron transfer throughout the cathode, resulting in superior electrochemical reactivity. At the cathode, the presence of Na2 CS3 forms an oligomer-structured layer to suppress the dissolution and shuttling of active materials. Meanwhile, when small portions of Na2 CS3 intermediates migrate to the anode, a stable solid electrolyte interphase (SEI) layer with uniform Na-ion flux is formed, enabling improved Na stripping and plating performance. A series of electrochemical and material characterization techniques, accompanied by density functional theory calculations, demonstrate that Na2 CS3 is a promising candidate to realize high-rate performance long cycle life RT Na–S batteries.